RAS Nanoclusters Selectively Sort Distinct Lipid Headgroups and Acyl Chains - Zhou, Yong; Gorfe, Alemayehu A.; Hancock, John F. (Frontiers in Molecular Biosciences, 2021)
RAS proteins are lipid-anchored small GTPases that switch between the GTP-bound active and GDP-bound inactive states. RAS isoforms, including HRAS, NRAS and splice variants KRAS4A and KRAS4B, are some of the most frequently mutated proteins in cancer. In particular, constitutively active mutants of KRAS comprise ~80% of all RAS oncogenic mutations and are found in 98% of pancreatic, 45% of colorectal and 31% of lung tumors. Plasma membrane (PM) is the primary location of RAS signaling in biology and pathology. Thus, a better understanding of how RAS proteins localize to and distribute in the PM is critical to better comprehend RAS biology and to develop new strategies to treat RAS pathology. In this review, we discuss recent findings on how RAS proteins sort lipids as they undergo macromolecular assembly on the PM. We also discuss how RAS/lipid nanoclusters serve as signaling platforms for the efficient recruitment of effector and signal transduction, and how perturbing the PM biophysical properties affect the spatial distribution of RAS isoforms and their functions.